Proliferasi Pemikiran Sosial Kritis: A Review Essay - Gunawan Wibisono (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Extract The genealogy of critical social thought finds its constitutive locus in the long-standing debates surrounding social science methodologies, from positivism to postmodernism and poststructuralism. This book delineates the framework of critical humanities knowledge while simultaneously engaging with a wide array of contemporary social issues. Although grounded in sociological reasoning, the book adopts an interdisciplinary perspective, addressing themes such as medical regimes, the political economy of higher education, and the vulnerabilities of digital subjects. These include challenges such as data concentration, surveillance capitalism, algorithmic power, and the logic of sharing economies within digital capitalism. The urgency of this publication lies in its potential to balance discourses of development with emancipatory and democratic ideals while also providing an academic impetus to strengthen civil supremacy in society.